Share ICT Training (E-Education Component) - Jaya Laxshmi, Meenatchisundaram (Institute of Social Informatics and Technological Informations, 2014)
A team of UNIMAS members went to Tanah Datar, West Sumatera, Indonesia from 21 – 23December 2014 to conduct the final workshop for the ICT training (e-Education component). The UNIMAS team members included Associate Prof. Dr Fitri Suraya Mohamad, Prof. Dr Alvin Yeo Wee, Syaryfah Fazidawaty binti Wan Busrah, Adam Francis and Jaya Laxshmi.